2017
DOI: 10.1371/journal.pone.0182286
|View full text |Cite
|
Sign up to set email alerts
|

A possible association between dysphonia and sleep duration: A cross-sectional study based on the Korean National Health and nutrition examination surveys from 2010 to 2012

Abstract: BackgroundSleep is important in terms of good general health and appropriate sleep duration has been linked to quality-of-life. Dysphonia may impair communication and social relationships, and is thus also closely related to quality-of-life. No large-scale, cross-sectional epidemiological study of a sample representative of the population of an entire country has yet assessed the possible existence of a relationship between sleep duration and dysphonia.MethodsWe investigated a possible association between subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…One Korean study using 2010–2012 data from the Korean National Health and Nutrition Examination Survey(KNHANES) revealed that 5 sleep hours or less was significantly associated with self-reported dysphonia and long-term dysphonia compared to 7 sleep hours: aOR = 1.45 (1.15–1.83), ≥ 3 weeks aOR = 1.57 (1.20–2.25), respectively [ 42 ]. Another study of teachers showed that there was a significant association between hoarseness and less than 6 sleep hours after adjustment for teaching career [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…One Korean study using 2010–2012 data from the Korean National Health and Nutrition Examination Survey(KNHANES) revealed that 5 sleep hours or less was significantly associated with self-reported dysphonia and long-term dysphonia compared to 7 sleep hours: aOR = 1.45 (1.15–1.83), ≥ 3 weeks aOR = 1.57 (1.20–2.25), respectively [ 42 ]. Another study of teachers showed that there was a significant association between hoarseness and less than 6 sleep hours after adjustment for teaching career [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…15,12 In South Korea, Cho reported a prevalence of 6.7%. 16 The prevalence of impairment in our sample using a cut-off of total VHI of 18 was 17.31% (8.23-30.32%). Cho's study 16 was a nationwide cross-sectional survey that was representative of the Korean population as it employed a more complex, stratified, multistage probability sampling design.…”
Section: Discussionmentioning
confidence: 66%
“…16 The prevalence of impairment in our sample using a cut-off of total VHI of 18 was 17.31% (8.23-30.32%). Cho's study 16 was a nationwide cross-sectional survey that was representative of the Korean population as it employed a more complex, stratified, multistage probability sampling design. Benninger's study 12 employed a large administrative database from which nationwide estimates were projected.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A estes somam-se os fatores ambientais, socioculturais, históricos, organizacionais, administrativos, sobrecarga de trabalho e relacionamento interpessoal.Como se pode observar, há uma complexa relação entre os fatores intrínsecos e extrínsecos para o desenvolvimento da disfonia. É possível que o envolvimento do professor com suas atividades laborativas, dentro e fora do ambiente de trabalho, assim como jornadas de trabalho exaustivas, já que essa categoria pode desenvolver até 60 horas semanais, contribua para o seu baixo envolvimento com atividade física.A atividade física pode trazer benefícios para a saúde vocal, pois de acordo com Sataloff (1997) apud Steffani, Vieceli e Grasel(2011, p.1) a adequada capacidade respiratória está associada à maior eficiência de voz e assim, no caso de indivíduos que utilizam a voz como instrumento de trabalho, devido ao decréscimo normal da função respiratória com a idade, torna-se essencial um melhor condicionamento não apenas respiratório, mas também físico e da musculatura abdominal" SATALOFF (1997) apud STEFFANI, VIECELI e GRASEL(2011, p.1).Entretanto, os achados deste estudo não demonstraram diferença estatisticamente significativa entre os níveis de atividade física e a disfonia (p=0,798) Cho et al (2017),. avaliando uma amostra nacionalmente representativa de 17.806 adultos com o objetivo de investigar uma possível relação entre disfonia, duração do sono e covariáveis como a prática de atividade física regular, também não encontraram associação significativa (p=0,925); vale ressaltar que este estudo não avaliou exclusivamente professores.praticantes de atividade física podem ter menores níveis de estresse e tensão corporal e, consequentemente, vocal, o que sugere uma relação entre sedentarismo e disfonia.…”
unclassified